Role Of Life Style Factors In Determination Of Academic Achievement Among Adolescent Students (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed at examining the role of life style factors in determination of academic achievement among adolescents. Academic achievement was taken as dependent variable whereas life style factors have been taken as independent variable. For the current investigation, ‘Descriptive survey method’ was employed. ‘Multi-stage random sampling technique’ was used to select a sample of 500 (250 male adolescents + 250 female adolescents) sr. sec. school students from Rohtak, Sonepat & Panipat Districts of Haryana state. Academic achievement can be defined as the score obtained by the senior secondary school students on their previous annual examination i.e. 10th standard. The data was collected using Life style scale by Kaur And S.K. Bawa’(2010). It was found that female adolescent students score better in academics than male adolescents.  The present study also concluded that male adolescents are more health conscious, more oriented towards their career, more socially oriented while female adolescent students are more academic oriented, more family oriented and more trend seeking lifestyle. Thus, we can say that significance difference was found between male and female with respect to life style factors. Furthermore, it was found that health conscious life style and trend seeking lifestyle factors are negatively but significantly correlated with academic achievement and other factors i.e. academic oriented lifestyle, family oriented life style and socially oriented life styles are positively & significantly correlated with academic achievement.